2003
DOI: 10.1519/1533-4287(2003)017<0704:eoptar>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plyometric Training and Recovery on Vertical Jump Performance and Anaerobic Power

Abstract: We examined the effects of 2 plyometric training programs, equalized for training volume, followed by a 4-week recovery period of no plyometric training on anaerobic power and vertical jump performance. Physically active, college-aged men were randomly assigned to either a 4-week (n = 19, weight = 73.4 +/- 7.5 kg) or a 7-week (n = 19, weight = 80.1 +/- 12.5 kg) program. Vertical jump height, vertical jump power, and anaerobic power via the Margaria staircase test were measured pretraining (PRE), immediately po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 21 publications
0
22
0
2
Order By: Relevance
“… Toumi et al (2004) reported that plyometric training affected elongation step. Luebbers et al (2003) evaluated jumping training by using a box that improved muscular strength. Therefore, the combination of the aforementioned trainings is necessary.…”
Section: Discussionmentioning
confidence: 99%
“… Toumi et al (2004) reported that plyometric training affected elongation step. Luebbers et al (2003) evaluated jumping training by using a box that improved muscular strength. Therefore, the combination of the aforementioned trainings is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in some studies, increases of 3.8% in CMJ after a 12-week program of resistance and plyometric exercises (Marques et al, 2008) and an increment of 7% in VJ height for starters and nonstarters in women's volleyball after a strength program during off-season training (Fry et al, 1991) have been found. Thus, strength training seems to be an essential tool in developing VJ performance (Luebbers et al, 2003). Resistance training improves the muscle contractile mechanisms, maximal force capacity and the rate of force development (Rimmer and Sleivert, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Un total de 59 estudis van ser inclosos en un primer moment. Després del procés de selecció aplicat, explicat anteriorment, es van identificar 40 estudis que complien les condicions requerides (Adams et al, 1992;Alkjaer, Meylandk, Raffalt, Lundbye-Jensen, & Simonsen, 2013;Campillo, Andrade, & Izquierdo, 2013;Cetin & Ozdol, 2012, Chaouachi et al, 2013Chelly et al, 2010;Chimera et al, 2004;Diallo, Dore, Duce, & Van Praagh, 2001;Faigenbaum et al, 2007;Fatouros et al, 2000;Gehri et al, 1998;Holcomb et al, 1996;Ford et al, 1983;Impellizzeri et al, 2008;Khlifa et al, 2010;King & Cipriani, 2010;Kotsamanidis, 2006;Luebbers, 2003;Lyttle, Wilson, & Ostrowski, 1996;Maffiuletti, Dugnanit, Folz, Di Pierno, & Mauro, 2002;Makaruk, Winchester, Sadowski, Czaplicki, & Sacewicz, 2011;Malifaux, 2006;Martel et al, 2005;Matavulj et al, 2001;Miller et al, 2002;Newton et al, 1999;Newton, Rogers, Volek, Häkkinen, & Kraemer, 2006;Ploeg et al, 2010;Potteiger et al, 1999;Rahimi & Behpur, 2005;Rimmer & Sleiver, 2000;Sáez de Villareal et al, 2008;Sankey, Jones, & Bampouras, 2008;Stojanovic & Kostic, 2002;Trícoli, Lamas, Carnevale, & Ugrinowitsch, 2005;…”
Section: Selecció Dels Estudisunclassified
“…També cal destacar que aporten beneficis en l'estabilitat articular i milloren els índexs de lesions greus de genoll (Chimera, K. A. Swanik, C. B. Swanick, & Straub, 2004 Nombroses investigacions (Adams, 1992;Faigembaum et al, 2007;Gehri, Ricard, Keiner, & Kirkendall, 1998;Holcomb et al, 1996;Kotsamanidis, 2006;Luebbers et al, 2003;Malifaux, Francaux, Nielens, & Theisen, 2006;Markovic, 2007;Matavulj, Kukolj, Urgakovic, Tihanyi, & Jaric, 2001;Newton, Kraemer, & Häkkinen, 1999;Potteiger et al, 1999;Wilson, Newton, Murphy, & Humphries, 1993) han demostrat que l'EP produeix millores en l'alçada del salt. D'altra banda també hi ha autors (Canavan & Vescovio, 2004;Herrero, Izquierdo, Maffiuletti, & García-López, 2006;Miller, Berry, Bullard, & Gilders, 2002;Turner et al, 2003) que no van trobar-hi cap millora i fins i tot hi ha altres estudis on es van donar resultats negatius (Luebbers et al, 2003). Tanmateix, certs autors (Blakey & Southard, 1987;Fatouros et al, 2013) estan d'acord en què per optimitzar els resultats d'un EP, aquest ha de combinar-se amb altres mètodes d'entrenament.…”
Section: Introduccióunclassified